PENGARUH PENGGUNAAN METODE PEMBELAJARAN LUAR RUANGAN PADA KELAS 1 DI SDN KEDUNGLUMPANG MOJOAGUNG - Qatrunnada, Nadia; Supratno, Haris; Siswanto, M. Bambang Edi (IJPSE : Indonesian Journal of Primary Science Education, 2020)
The method of learning outside the classroom based on problem solving is a learning activity that takes place outside the classroom that involves a variety of problem solving activities. In this case the research is focused on how student learning outcomes in the classroom use the lecture method, how student learning outcomes with methods of learning outside the classroom based learning problem solving, as well as how the influence of learning methods outside the classroom based on problem solving on student learning outcomes. By knowing this the researcher aims to be able to contribute to the learning methods in schools so that the method can be applied in schools and can benefit both parties.Researchers use quantitative methods. This research was conducted at SDN Kedulumpang Mojoagung in 2 classes with 25 students in each class. Data collection used in this study are: observation and written test. Observations were made during the learning activities took place and the written test was carried out after the learning activities. Researchers validate all instruments used to education experts before the research instruments are used. Analysis of the data collected in this study uses perametric and non-parametric data analysis.Based on the analysis of the data obtained shows that the control class get good value criteria by getting an average grade of 72, while for the experimental class get very good criteria by obtaining a class average value of 84. Researchers also do man whitney analysis because the data berdistribisi obtained is not normal, indicating that the mean rank class experiment more substantial than classroom control and value Asympotic Significancy ujinya worth 0.004 or more smaller than the level of real 5%. It is demonstrated that the value of the exam students classroom experiment is higher than the value of the exam students grade control . so it can be concluded that the outdoor learning method based on problem solving can have a positive influence on student learning outcomes.